Gene network variation and alternative paths to convergent evolution in turtles. Issue 5 (9th August 2018) - Cordero, Gerardo A.; Liu, Haibo; Wimalanathan, Kokulapalan; Weber, Rachel; Quinteros, Kevin; Janzen, Fredric J.
Abstract : Diversification of the turtle's shell comprises remarkable phenotypic transformations. For instance, two divergent species convergently evolved shell‐closing systems with shoulder blade (scapula) segments that enable coordinated movements with the shell. We expected these unusual structures to originate via similar changes in underlying gene networks, as skeletal segment formation is an evolutionarily conserved developmental process. We tested this hypothesis by comparing transcriptomes of scapula tissue across three stages of embryonic development in three emydid turtles from natural populations. We found that alternative strategies for skeletal segmentation were associated with interspecific differences in gene co‐expression networks. Notably, mesenchyme homeobox 2 (MEOX2) and HOXA3‐5 were central hubs driving the activity of 2, 806 genes in a candidate network for scapula segmentation, albeit in only one species. Even so, scapula muscle overgrowth corresponded to the activity of similar myogenic networks in both species. This and other derived developmental processes were not observed in the third species, which displayed the ancestral (unsegmented) scapula condition. Differential gene expression tests against this reference lineage supported histological and network analyses. Our findings illustrate that molecular underpinnings of convergent evolution, including during the diversification of the atypical turtle "body plan, " are influenced by variation in underlying developmental processes.